SISTEM INFORMASI WEBSITE OUTSOURCING SECURITY MENGGUNAKAN FRAMEWORK LARAVEL SEBAGAI SARANA INFORMASI DAN PENAWARAN SECURITY PADA PT. GARUDA ELANG SAKTI (GES) - Zulyanto Ilham Nurrahman (2022)
Many things, such as online commerce, are evolving as a result of technological advances. It is easier for consumers to make offers without having to leave the house because nowadays there are so many online companies or businesses. This can be a concern widely used by entrepreneurs who do not have much free time to offer Outsourcing security. PT. Garuda Elang Sakti (GES) is one of the companies engaged in security services with very minimal marketing, companies that offer very few services and systems that are still in the conventional way make bidding quite difficult. The purpose of this design is to market the company through the website and streamline incoming offers using the waterfall method. The author does this design using HTML and CSS on the client page and then uses the PHP programming language and the Laravel framework and uses the MySql database to integrate data on the admin page, it is hoped that this system design can market the company and facilitate offerings effectively.